Quality of Life and Mental Health in Patients with Chronic Diseases Who Regularly Practice Yoga and Those Who Do Not: A Case-Control Study. (6th June 2013) - Cramer, Holger; Lauche, Romy; Langhorst, Jost; Dobos, Gustav; Paul, Anna
Abstract : While clinical trials have shown evidence of efficacy of yoga in different chronic diseases, subjective health benefits associated with yoga practice under naturalistic conditions have not yet been investigated. The aim of this study was to investigate associations of regular yoga practice with quality of life and mental health in patients with chronic diseases. Using a case-control design, patients with chronic diseases who regularly practiced yoga were selected from a large observational study and compared to controls who did not regularly practice yoga and who were matched individually to each case on gender, main diagnosis, education, and age (within 5 years). Patients' quality of life (SF-36 questionnaire), mental health (Hospital Anxiety and Depression Scale), life satisfaction, and health satisfaction (Questionnaire for Life Satisfaction) were assessed. Patients who regularly practiced yoga (n = 186 ) had a better general health status (P = 0.012 ), a higher physical functioning (P = 0.001 ), and physical component score (P = 0.029 ) on the SF-36 than those who did not (n = 186 ). No group differences were found for the mental scales of the SF-36, anxiety, depression, life satisfaction, or health satisfaction. In conclusion, practicing yoga under naturalistic conditions seems to be associated with increased physical health but not mental health in chronically diseased patients.